Benthic amphipods (Amphilochidea and Senticaudata) in the northern central peruvian continental shelf - Jiménez, Analí (2018)
In this work, amphipod species of the suborder Amphilochidea and Senticaudata from the North-Central Continental Platform of Peru (03°24'S - 79°30'W to 09°00'S - 81°30'W) are reported. 136 stations were sampled, range between 22 to 372 m in depth, all collections were during the autumn. We determined 28 species, belonging to 15 families. Ampeliscidae family was the most diverse with eleven (11) species. Of the total of species, 14 species are new records to Peruvian sea. Indeed, this research includes descriptive taxonomic information and referenced geographical distribution.